2006
DOI: 10.1007/s00467-006-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe renal artery stenosis by percutaneous transluminal renal angioplasty and stent implantation

Abstract: The clinical course of two children with mid-aortic syndrome and renal artery stenosis (RAS) who suffered from severe arterial hypertension is described. Hypertension was uncontrollable by antihypertensive medication and was managed by percutaneous transluminal renal angioplasty (PTRA) with stent implantation. The pediatric experience with PTRA is limited, and there are only few cases reported with additional stent implantation. Complications of these procedures are well known from experience with adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 109 publications
(53 reference statements)
4
30
0
4
Order By: Relevance
“…In cases, angioplasty had been reported as very useful, but other authors have reported poor long-term results needing the use of stents [1,[10][11][12][13][14][15]. In our patient, the angioplasties performed obtained an excellent immediate result, but really poor intermediate or long-term results.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…In cases, angioplasty had been reported as very useful, but other authors have reported poor long-term results needing the use of stents [1,[10][11][12][13][14][15]. In our patient, the angioplasties performed obtained an excellent immediate result, but really poor intermediate or long-term results.…”
Section: Discussionmentioning
confidence: 43%
“…This can be achieved through percutaneous angioplasty and surgical interventions. In severe cases, where none of the previous treatments is successful, a nephrectomy is an alternative [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations